Efektivitas Pupuk Hayati dan Pupuk Kotoran Sapi Terhadap Pertumbuhan Serta Produksi Tanaman Pakcoy (Brassica rapa L.) - Putra, Irwansyah; Sari Sembiring, Desi Sri Pasca; Amrul, Hanifah Mutia Z N (JURNAL AGROPLASMA, 2024)
Pakcoy plants have an economic aspect and the business is worth developing or cultivating to meet consumer demand which is increasing over time. Increasing the production of pakcoy plants can be done by improving the fertility of the planting medium by using FertoMax biofertilizer and cow dung fertilizer. This research used a Randomized Block Design with 2 factors and 3 replications to obtain 48 research plots. Factor I of FertoMax Biological Fertilizer (S) which consists of 4 levels, namely: S0 = 0 ml/polybag, S1 = 5 ml/polybag, S2 = 10 ml/polybag, S3 = 15ml/polybag. Factor II Cow Manure (P) which consists of 4 levels, namely: P0 = 0 g/polybag P1 = 100 g/polybag, P2 = 200 g/polybag, P3= 300 g/polybag. The parameters observed in this study were plant height, number of leaves, leaf length, leaf width, tuber diameter, sample plant weight, plant weight per plot. The results of the study showed that the use of FertoMax biofertilizer with the best growth and production was at a dose of 15 ml/polybag while giving The best dose of cow dung fertilizer is 300 g/polybag. Keywords: pakcoy, fertomax biological fertilizer, cow manure